Pediococcus Acidilactici NRRL B-50517 as a Safe Probiotic for Regulation of Weight Related Pro-inflammatory Cytokines: A Double-blind Placebo-controlled Pilot Study (P21-026-19). (13th June 2019) - Lin, Jhy Jhu; O'Connell, Jeanne; Sinclair, Steve
Abstract: Objectives: Development of a probiotic P. acidilactici NRRL B-50517 that resists to high temperature (up to 85 ° C), stomach acids, and air. Clinic evaluation of P. acidilactici NRRL B-50517 as a safe probiotic for regulation of weight related pro-inflammatory cytokines. Methods: Survival studies were conducted by incubating P. acidilactici NRRL B-50517 in either liquid MRS broth, pH1.5 at 85°C overnight, or in dried powder at 85°C for 5–10 minutes. Healthy volunters were randomly assigned two capsules of placebo or Pediococcus probiotics (4 billion CFU) daily for three months. Biweekly phone interviews with 30 participants were performed to ensure daily dosage administration, and to collect the results of the questionnaire related to 6 categories of gut functions. Percent body fat measurements and serum were collected upon study initiation and completion. Serum was processed for cytokine analysis by multiplex ELISA assays. Results: P. acidilactici NRRL B-50, 517 survived at 85°C and pH 1.5 in MRS broth and dried powder forms. No statistical significantly changes of gut functions between the placebo group and the probiotic group in appetite: t -value 1.6808, p-value 0.1313; energy level: t -value 0.7508. p-value 0.5003; bowel movement: t -value 0.3348. p-value 0.7464; stool quality: t -value 0.6929, p-value 0.5080; bloating: t -value 2.0583. p-value 0.0736; gas t -value: 1.9560, p-value 0.0875. On average, the probiotic lost 0.86% ± 0.42% body fat whereas the control group gained 0.28% ± 0.19, P  = 0.0264. Pro-inflammaroty IL-6 ratios differed by 0.61 ± 0.22 and 3.06 ± 0.87 in the probiotic and control groups, respectively ( P  = 0.0295); pro-inflammatory IL23 ratio was 0.65 ± 0.14 in the probiotic and 1.71 ± 0.38 in the control group, P  = 0.0068. Conclusions: Novel P. acidilactici NRRL B-50, 517 is safe for human consumption and may be useful in reducing body fat and pro-inflammatory markers. Funding Sources: TEDCO, Maryland.